2016
DOI: 10.1167/iovs.16-20162
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin/CBP–Dependent Signaling Regulates TGF-β–Induced Epithelial to Mesenchymal Transition of Lens Epithelial Cells

Abstract: PurposeTransforming growth factor-β–induced epithelial–mesenchymal transition (EMT) is one of the main causes of posterior capsular opacification (PCO) or secondary cataract; however, the signaling events involved in TGF-β–induced PCO have not been fully characterized. Here, we focus on examining the role of β-catenin/cyclic AMP response element–binding protein (CREB)-binding protein (CBP) and β-catenin/T-cell factor (TCF)-dependent signaling in regulating cytoskeletal dynamics during TGF-β–induced EMT in lens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 59 publications
1
33
0
Order By: Relevance
“…Overall, the current study in lens epithelial explants demonstrates that the progression of TGFβ-induced demonstrated that β-catenin-mediated signaling, specifically when in complex with CREB-binding protein, is required for TGFβ-induced EMT, outlining a manner in which the effects of EMT are propagated in a feed-forward loop (66). Therefore, our findings demonstrate a …”
Section: Discussionsupporting
confidence: 52%
“…Overall, the current study in lens epithelial explants demonstrates that the progression of TGFβ-induced demonstrated that β-catenin-mediated signaling, specifically when in complex with CREB-binding protein, is required for TGFβ-induced EMT, outlining a manner in which the effects of EMT are propagated in a feed-forward loop (66). Therefore, our findings demonstrate a …”
Section: Discussionsupporting
confidence: 52%
“…ERK1/2, a type of MAPK, has been implicated as an important component in many signaling systems containing polymethoxylated flavones involved in various biological functions, such as the differentiation and lipolysis of adipocytes, neurotrophic action, and MMP expression. 14,26,27) In lens epithelial cells, ERK1/2 was reported to be involved in the TGFβ-induced EMT 28) ; therefore, 5,7-dimethoxyflavone may inhibit the EMT in TGFβtreated LECs, and lead to the visual impairments observed in ASC and PCO. The relationship between the expression of MMP-9 and the EMT, and the regulation of this by KPMFs, should be investigated further in the future.…”
Section: Discussionmentioning
confidence: 99%
“…At first, β-elemene (Sigma-Aldrich, St. Louis, MO) was tested for its independent effects at six doses (5,10,20,40,80, and 160 μg/ml) for 24 h and 48 h. The phosphotidylinsitol-3-kinase (PI3K) inhibitor LY294002 (Sigma) and protein kinase B (Akt) inhibitor MK2206 (Sigma) were dissolved in dimethyl sulfoxide. The working concentrations of LY294002 and MK2206 were 10 μM and 1 μM, respectively, as previously described [29][30][31]. With or without pretreatment with the above inhibitors for 1 h, VSC4.1 motor neurons were exposed to β-elemene (20 μg/ml) for 24 h. Chemical hypoxic injury of VSC4.1 motor neurons was then induced by CoCl 2 (Sigma) in a dose-dependent manner (150, 300, 400, 500, 600, and 1200 μM) for 24 h. Then, VSC4.1 motor neurons were pretreated with 20 μg/ml β-elemene for 4 h to observe its protective effects on CoCl 2 (400, 500, and 600 μM)-induced cellular damage.…”
Section: Methodsmentioning
confidence: 99%